Significance of Fast in Blunt Abdominal Trauma - Hinbis Masawod, Amir; Jabbar Kashtal, Hazim; Modher Khalaf , Ahmed (Diyala Journal of Medicine, 2020)
Background: Blunt abdominal trauma is a common problem in our country.Some of the cases had been explored on no bases which were negative by FAST(focused assessment with sonography of trauma)FAST is a tool to detect intra-abdominal collection. Objective: To appreciate the value of (FAST) in blunt abdominal trauma. Patients and Methods: This study performed by a collection of 100 cases of blunt abdominal trauma admitted to the emergency department at Baquba Teaching Hospital from the period 1st January, 2013 to 31st December 2013 fast performed on all cases to detect any intra-abdominal collection, then correlation with this result and laparotomy or conservative results. Results: Out of 100 patients, Twenty seven cases had intra-abdominal collection and seventy three cases had no intra-abdominal collection by fast, 27 cases were positive and one case false positive and 73 cases were negative and 2 false-negative results and 71 true negative. The sensitivity was 92.8 % and specificity 98.6%. The positive predictive value was 96.2 % and negative predictive value 97.2 % and the accuracy 97 %. Conclusion: Focused assessment sonography of trauma can detect intra-abdominal fluid accurately and rapidly, FAST potentially valuable tool for better assessment of trauma in the emergency department.